Business intelligence and information systems : which are the strategic and managerial impacts linked to the use of a business intelligence or information systems technologies? - Costa, Daniel da (2015)
In this context of globalized crisis, companies have to invest in optimal technologies, in order to choose the right strategy. The following thesis is oriented in the aim to study and understand what are the managerial impacts linked with the use of Information Systems and Business Intelligence. To study this phenomenon, I have decided to develop a qualitative research method. I was then able to face different concepts before indeed reaching my goal which is to find an answer to the problematic and study. From a theoretical point of view, after reading and analyzing specialized books and sciences articles, the investigated field offers a new way of understanding and studying a managerial phenomenon. As a result, the suggested research methodology defines a new concept of understanding the enterprises and the managerial impacts resulting from the use of those technologies. From a managerial point of view, researches have shown that the payroll and infrastructures have a key role with the aim of increasing and evolving as a group. Therefore, this thesis has demonstrated the importance of implementing quality and standards in each process. This thesis allows me to present an essential feature to a successful implantation and use of those tools: the culture of the company.